Two teachers and a half. Reflections about the teacher in the Spanish culture of twentieth century (Journal of Parents and Teachers, 2012)
Spain hasn’t been able to enabling a fundamental consensus about national education like the other big European nations. As Ortega suggested, a left-wing that doesn’t believe in culture sees the teacher just as a publicist of an ideal republic. A right-wing, on the other hand, doesn’t have a model of public education and because of that identifies itself with the educational concert. Under these two dysfunctions are hidden philosophical cartoon of the way of teaching that are trying to be clarified.
Keywords: Propaganda and culture; family-state relation; philosophy of education; pedagogy of philosophy